Toward a Theory of Community-Based Enterprise - Peredo, Ana María; Chrisman, James J. (Academy of Management Review, 2006)
In this article we develop the concept of community-based enterprise (CBE) and argue that it provides a potential strategy for sustainable local development in poor populations. We maintain that in this emerging form of entrepreneurship, typically rooted in community culture, natural and social capital are integral and inseparable from economic considerations, transforming the community into an entrepreneur and an enterprise. Drawing on interdisciplinary and multilevel approaches, we propose a theoretical model of the determinants, characteristics, and consequences of CBEs.